A STUDY ON LINGUISTIC ETHNOGRAPHY OF TEACHING-LEARNING ENGLISH IN ELT CLASSES: THE CASE OF HINDE JUNIOR SCHOOL - Duresa, Misgana (LLT Journal: A Journal on Language and Language Teaching, 2024)
The study intended to explore the linguistic ethnography of teaching and learning English in English language teaching classes. An ethnographic case study design was employed on three English teachers. The school and teachers were selected purposively. Both observation and interview questions were given to language experts to ensure the validity and reliability of the tools. Teachers were observed and interviewed, and notes were taken. Following, data was collected, coded, categorized, and analyzed thematically. The Cultural Activity Theory (CHAT) model was used, and intervention was made. The result of the study revealed that English lesson provision in Hinde Junior School was dominated by traditional teaching. In contrast, communicative and participatory teaching was left out because of the absence of eclectic teaching methods, large class sizes, and a shortage of English textbooks. However, intervention was provided. Teachers were provided with training and support for their students to increase their use of effective and varied teaching methods. As a result, changes were seen, and teachers could use eclectic and participatory teaching methods. Besides, extra books were borrowed from the neighboring schools and provided to students. For large class size-related problems, a discussion was held with the school, and these problems were solved with the community and other concerned bodies.   Therefore, teachers’ training on the application of eclectic teaching methods and student support should be provided, whereas books should be borrowed from other schools. Schools, community, and other concerned bodies should work collaboratively to overcome problems related to large class sizes.